On critical parameters of photonuclear isotope production - Uvarov, V.L. (Вопросы атомной науки и техники, 2019)
Analytical model for description of isotope generation in a thick production target exposed to no uniform flux of high-energy bremsstrahlung radiation is developed. A set of principal process parameters determinative the yield of a product isotope and distribution of its specific activity has been established. It is shown, that as those parameters may be the yield of the product isotope in a thin foil overlapping the photon flux, normalized to the mass thickness of the foil (a coefficient of photonuclear conversion), and also the standard radial deviation of the flux density of the above-threshold photons at the target as well as the most probable angle of their escape from a bremsstrahlung converter. The methods for measuring those parameters are proposed. Testing of the model was conducted using the ¹⁰⁰Мо(y,n)⁹⁹Mo reaction by comparing the results obtained from the model consideration with the data of experimental study and computer simulation. The proposed approach enables the optimization of photonuclear technology as respects to target dimensions and activation regime. Запропоновано аналітичну модель для опису генерації ізотопів у товстій технологічній мішені під дією просторово-неоднорідного потоку високоенергетичного гальмівного випромінення. Встановлено набір основних параметрів процесу, що визначають вихід цільового ізотопу і розподіл його питомої активності в мішені. Показано, що такими параметрами можуть бути нормований на масову товщину вихід цільового ізотопу в тонкій протяжній мішені, яка перекриває потік гальмівних фотонів (коефіцієнт фотоядерної конверсії), а також стандартний радіальний відхил розподілу щільності потоку надпорогових гальмівних фотонів на мішені і найбільш вірогідний кут їх вильоту з конвертера. Описані методи вимірювання цих параметрів. На прикладі реакції ¹⁰⁰Мо(y,n)⁹⁹Mo проведено тестування аналітичної моделі шляхом експериментального дослідження і комп'ютерного моделювання. Запропонований підхід дозволяє проводити оптимізацію фотоядерної технології відносно розмірів мішені і режиму її активації. Предложена аналитическая модель для описания генерации изотопов в толстой технологической мишени под воздействием пространственно-неоднородного потока высокоэнергетичного тормозного излучения. Установлен набор основных параметров процесса, определяющих выход целевого изотопа и распределение его удельной активности в мишени. Показано, что такими параметрами могут являться нормированный на массовую толщину выход изотопа в тонкой мишени, перекрывающей поток тормозных фотонов (коэффициент фотоядерной конверсии), а также стандартное отклонение радиального распределения плотности потока надпороговых фотонов на мишени и наиболее вероятный угол их вылета из конвертера. Описаны методы измерения этих параметров. На примере реакции ¹⁰⁰Мо(y,n)⁹⁹Mo проведено тестирование модели путем сравнения полученных на ее основе данных с результатами экспериментального исследования и компьютерного моделирования. Предложенный подход позволяет производить оптимизацию фотоядерной технологии производства изотопов в отношении размеров мишени и режима ее активации.